2006
DOI: 10.1074/jbc.m600514200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Stimulates Cyclin D1 Expression through Activation of β-Catenin Signaling in Chondrocytes

Abstract: Transforming growth factor-␤ (TGF-␤) plays an essential role in chondrocyte maturation. It stimulates chondrocyte proliferation but inhibits chondrocyte differentiation. In this study, we found that TGF-␤ rapidly induced ␤-catenin protein levels and signaling in murine neonatal sternal primary chondrocytes. TGF-␤-increased ␤-catenin induction was reproduced by overexpression of SMAD3 and was absent in Smad3 ؊/؊ chondrocytes treated with TGF-␤. SMAD3 inhibited ␤-transducin repeat-containing protein-mediated deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 36 publications
9
83
0
Order By: Relevance
“…[32][33][34][35] In the present study, we demonstrated a novel role of ␤-catenin in mediating TGF-␤1-induced myofibroblast differentiation in VICs. We showed that TGF-␤1-induced ␣SMA transcription and myofibroblast differentiation were dependent on the availability of ␤-catenin.…”
Section: Tgf-␤1-induced ␤-Catenin Nuclear Translocation and Myofibrobmentioning
confidence: 73%
“…[32][33][34][35] In the present study, we demonstrated a novel role of ␤-catenin in mediating TGF-␤1-induced myofibroblast differentiation in VICs. We showed that TGF-␤1-induced ␣SMA transcription and myofibroblast differentiation were dependent on the availability of ␤-catenin.…”
Section: Tgf-␤1-induced ␤-Catenin Nuclear Translocation and Myofibrobmentioning
confidence: 73%
“…For example ␤-catenin regulates wound size and mediates the effect of TGF-␤ in cutaneous healing (46). Cooperation between ␤-catenin and TGF-␤1 signaling has also been demonstrated in chondrocytes, playing a key role in chondrocyte differentiation, suggesting that integration of these signaling pathways are important in controlling endochondrial ossification (47,48). Smad-3-dependent nuclear translocation of ␤-catenin is also required for TGF-␤1-induced proliferation of bone marrow-derived adult human mesenchymal stem cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, undifferentiated stem cells were used, and the effect of b-catenin was delivered in concert with TGFb-activation. TGFb plays an essential role in stimulating chondrocyte proliferation and the inhibition of chondrocyte hypertrophic differentiation, in which the former was shown to be through the b-catenin signaling-dependent cyclin D1 expression [46,47]. It is likely that with the continuous co-activation of b-catenin, MSCderived chondrocytes were maintained in the proliferative, prehypertrophy stage via the action of cyclin D1.…”
Section: Discussionmentioning
confidence: 99%